2006
DOI: 10.1111/j.1462-2920.2005.00948.x
|View full text |Cite
|
Sign up to set email alerts
|

A new green fluorescent protein‐based bacterial biosensor for analysing phenanthrene fluxes

Abstract: The polycyclic aromatic hydrocarbon (PAH)-degrading strain Burkholderia sp. RP007 served as host strain for the design of a bacterial biosensor for the detection of phenanthrene. RP007 was transformed with a reporter plasmid containing a transcriptional fusion between the phnS putative promoter/operator region and the gene encoding the enhanced green fluorescent protein (GFP). The resulting bacterial biosensor--Burkholderia sp. strain RP037--produced significant amounts of GFP after batch incubation in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…It has been reported that the solubility of PHE in water is about 1.1-1.2 mg/l [5,6]. However, in the process of PHE biodegradation, the concentration of PHE is depleted with incubation time while more PHE may be soluble till the substrate is exhausted.…”
mentioning
confidence: 97%
“…It has been reported that the solubility of PHE in water is about 1.1-1.2 mg/l [5,6]. However, in the process of PHE biodegradation, the concentration of PHE is depleted with incubation time while more PHE may be soluble till the substrate is exhausted.…”
mentioning
confidence: 97%
“…in the concentration range from 200 nM to 1.2 mM (Wei et al 2010), whereas BMB-PL was weakly induced by naphthalene, salicylate and pyruvate (data not shown). It was assumed that no induction would occur in the presence of other PAHs whose solubility in water is even lower than PHE (0.076 mg L -1 ) (Tecon et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…To run 20 parallel microcosms, obtain 100 ml of modified tryptone-yeast medium (mTY) 14 , about 150 ml of 21C minimal medium 16 (MM), 5 ml of minimal medium agar (MMA; 0.5%, w/v), three potato dextrose agar plates (PDA; 1.5%, w/v) for P. ultimum, four blank plates, one PDA plate containing 2 mg L -1 cycloheximide, four agarose plates (3%, w/v) containing 0.3 g ml -1 activated carbon and 40 mg of FLU in 2 mg portions. 2.…”
Section: Preparation Of Media and Culturesmentioning
confidence: 99%
“…In more detail, three-ring PAH fluorene, the mycelial organism Pythium ultimum and the bioreporter bacterium Burkholderia sartisoli RP037-mChe 13 were applied in the described microcosm setups. The bacterium B. sartisoli RP037-mChe was originally constructed to study phenanthrene fluxes to the cell 14 and expresses enhanced green fluorescent protein (eGFP)…”
Section: Introductionmentioning
confidence: 99%